The levels of p53 govern the hierarchy of DNA damage tolerance pathway usage - Castaño, Bryan A. (2024)
It is well-established that, through canonical functions in transcription and DNA repair, the tumor suppressor p53 plays a central role in safeguarding cells from the consequences of DNA damage. Recent data retrieved in tumor and stem cells demonstrated that p53 also carries out non-canonical functions when interacting with the translesion synthesis (TLS) polymerase iota (POLι) at DNA replication forks. This protein complex triggers a DNA damage tolerance (DDT) mechanism controlling the DNA replication rate. Given that the levels of p53 trigger non-binary rheostat-like functions in response to stress or during differentiation, we explore the relevance of the p53 levels for its DDT functions at the fork. We show that subtle changes in p53 levels modulate the contribution of some DDT factors including POLι, POLη, POLζ, REV1, PCNA, PRIMPOL, HLTF and ZRANB3 to the DNA replication rate. Our results suggest that the levels of p53 are central to coordinate the balance between DDT pathways including (i) fork-deceleration by the ZRANB3-mediated fork reversal factor, (ii) POLι-p53-mediated fork-slowing, (iii) POLι- and POLη-mediated TLS and (iv) PRIMPOL-mediated fork-acceleration. Collectively, our study reveals the relevance of p53 protein levels for the DDT pathway choice in replicating cells.